Analisis Yuridis Dimensi Pertanggungjawaban Hukum Atas Pembatalan Nikah Untuk Meneguhkan Kepastian Hukum - Muzahar, Muzahar; Ida, Ansharullah; Erniyanti, Erniyanti (Jurnal Syntax Fusion, 2022)
This study aims to find out and analyze the implementation of legal responsibility for marriage annulment in Decision Number: 245/Pdt.G/2021/PA.Btm. To find out and analyze Decision Number: 245/Pdt.G/2021/PA.Btm regarding legal liability for marriage annulment by the Religious Courts to strengthen legal certainty. This study uses a descriptive analytical research type method using an empirical juridical approach. The results of the study show that the implementation of legal responsibility for marriage annulment in Decision Number: 245/Pdt.G/2021/PA.Btm did not run optimally because the Respondent never attended the trial process and the Panel of Judges made a decision by granting the Petitioner's request with verstek, and declaring null and void The marriage of the Petitioner and Respondent was held on September 19 2020 before the Marriage Registrar of the Office of Religious Affairs (KUA). Analysis of Decision Number: 245/Pdt.G/2021/PA.Btm on legal responsibility for canceling marriages by the Religious Courts to confirm legal certainty, namely that the cancellation of marriages can be accounted for and realized to strengthen legal certainty. This is because the Petitioner in this case has fulfilled all the requirements specified for annulment of marriage. Apart from that, the annulment of the marriage which was granted by the Panel of Judges also provided a sense of justice for the Petitioner, who so far had the right to receive spiritual support but the Respondent as a married couple was unable to fulfill it. For this reason, it is recommended for couples who want to get married to be open to each other about each other's shortcomings. To parents to carefully consider every process of applying for an annulment of marriage, and try to maintain their children's household as best as possible and to the Panel of Judges to consider the decision as fair as possible and ensure the wishes of both parties